Reconstruction of the islamic human development index in Indonesia through principal component analysis (PCA) - Maulana Kamal Arsyad; Achmad Sani Supriyanto; Vivin Maharani Ekowati (Faculty of Islamic Economics and Business UIN Salatiga, 2025)
This study examines the construct validity of the Islamic Human Development Index (IHDI) indicators proposed by Anto (2011) and Rama and Yusuf (2019) in the context of Indonesia’s human development. Using Principal Component Analysis (PCA) and secondary data from 34 provinces in 2024, the study finds that two indicators the zakat to GRDP ratio and the Gini ratio were excluded due to high regional variability. Four principal components emerged, representing socio-religious aspects, quality of life, economic welfare, and social mobility, explaining 75.72% of the variance. The findings reveal that human development in Indonesia emphasizes spiritual, social, and economic balance but lacks full alignment with maqāṣid al-sharī‘ah principles of equity and justice. Zakat, despite being a key Islamic economic pillar, remains empirically weak due to institutional and data limitations, highlighting the need to strengthen zakat governance for effective redistribution and welfare enhancement.